Lanthanide bioadsorption by the extremophile Exiguobacterium sp.: utilizing microbial extracellular polysaccharides for high-value element recovery - Karem Gallardo; Génesis Serrano; Rodrigo Castillo; Sebastián Michea; Julio I. Urzúa; Dayana Arias; Francisco Remonsellez; Francisco Remonsellez (Frontiers in Microbiology)
Rare Earth Elements (REEs) are essential components in modern technologies but are challenging to extract sustainably. With increasing demand and limited supply, alternative recovery methods such as biosorption have gained attention. In particular, biosorption using extracellular polymeric substances (EPS) offers a promising and environmentally friendly approach. This study explores the potential of Exiguobacterium sp. SH31, an EPS-producing extremophilic strain, for the biosorption of six REEs (Y, Pr, Nd, Gd, Tb, and Dy) commonly found in spent mobile phones. EPS production and biofilm formation were evaluated in the presence of REEs at concentrations of 0.1 mM and 1 mM, and at pH values of 7, 7.5, and 8. Biosorption capacity was assessed, and characterization was performed using attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and transmission electron microscopy (TEM). EPS were extracted using ultrasound and EDTA-based protocols for compositional analysis. The SH31 strain tolerated up to 1 mM REEs at all tested pH levels with minimal physiological changes. EPS production increased slightly in the presence of metals, with compositional variations dependent on extraction method and pH. Ultrasound-extracted EPS showed higher polysaccharide content at pH 7 and increased nucleic acids at pH 8, while EDTA-extracted EPS had more proteins at pH 7 and nucleic acids at pH 8. Biofilm formation increased in the presence of metals at pH 7 and was overall higher at pH 8, although reduced compared to the control. Adsorption capacity peaked at pH 8, reaching 87–99% for all REEs, and fitted well to the Langmuir isotherm model, indicating monolayer biosorption. Desorption efficiencies ranged from 30 to 90%, depending on the metal, pH, and concentration. ATR-FTIR analysis identified hydroxyl and carbonyl groups as key functional groups involved in metal binding, with notable spectral changes after REE exposure. TEM images revealed cell surface deformation and nanoparticle formation, but no intracellular metal accumulation, confirming that adsorption occurs through EPS-mediated surface binding rather than bioaccumulation. These findings highlight the potential of Exiguobacterium sp. SH31 for REE recovery from e-waste leachates, contributing to sustainable electronic waste revalorization strategies.